PENYULUHAN EDUKASI TEKNIK AKUPRESUR TERHADAP TINGKAT PENGETAHUAN IBU DI KEC. SIANTAR TIMUR - I Ngurah Gede Verar Fujastawan; Yeni Trisna Purba; Rizky Randa Ritonga (Nusantara Hasana Journal, 2025)
The educational outreach on acupressure techniques is a community service initiative aimed at improving mothers' knowledge and understanding of the benefits of acupressure in supporting health. This activity was conducted in the Siantar Timur District using interactive approaches such as lectures, live demonstrations, and the distribution of educational leaflets. Based on literature studies, acupressure techniques have been widely applied as a non-invasive method to address various physical and mental complaints, such as stress, pain, and digestive disorders. This paper presents the framework of the outreach program, situational analysis, implementation methodology, pre- and post-questionnaire evaluation results, and a discussion on the effectiveness of the outreach. The findings indicate a significant increase in participants’ knowledge after attending the outreach, as well as long-term potential benefits for mothers’ health